Molecular Phylogeny of Phytoremediator aquatic weed Pistia stratiotes L. by rbcLa Barcoding from Balloki Headworks, Punjab, Pakistan - Wasim Abbas; Maryam Iqbal; Zaheer-ud-din Khan; Muhammad Umer Farooq Awan (Journal of Animal and Plant Sciences, 2025)
Pistia stratiotes L. is a pantropical aquatic weed, also known as water lettuce. It is native to tropical and subtropical lakes of Brazil and Chile. It is a floating stoloniferous plant that can influence aquatic ecosystems and limnological characteristics. Pistia stratiotes L. can be used to improve the quality of water and decrease the risk of eutrophication in aquatic ecosystems. Despite its ecological significance as a phytoremediator and its invasive distribution, it is necessary to investigate genotypic plasticity. The current study focuses on the molecular identification of Pistia stratiotes L. and explores its phylogenetic relationship with closely related species. Specific primers for rbcLa were applied for PCR amplification. PCR products after purification were subjected to rbcLa sequence barcode. Chromas was applied to analyse the chromatogram file. Sequence alignment was completed by multiple sequence alignment (MSA) and Clustal 2.1. Basic Logical Alignment Sequence Tool (BLAST) of the NCBI database was used to align the query sequence. The rbcLa marker barcode showed 99.46% accuracy for the identification of species. The DNA barcode based phylogenetic tree revealed that Pistia stratiotes L. is the only surviving specie of this genus and its closest relative is Hydrilla verticillata (L.f.) Royale belonging to the family Hydrocharitaceae.
Keywords: Aquatic Ecosystems; DNA barcode; rbcLa; Hydrophytes; Phylogeny